Potential Health Hazards of Roadside Springs: Results from Central New York. (14th October 2021) - Sinton, Christopher W.; Olivieri, Matthew; Perry, Tara; Stoddard, Katherine; Kresge, Ryan
Abstract: Across the United States, groundwater springs adjacent to roadways have been developed as unregulated drinking water sources. We attempted to address two basic questions: 1) why do people collect water at these springs; and 2) is the water safe to drink? We conducted a study during 2015‐2019 of seven springs in central New York State that included a survey of 199 users and analysis of the water for common dissolved constituents and bacteria. The survey of water users showed that over 70% of respondents use the springs at least multiple times per month for drinking water and the majority collect more than five gallons per visit. More than 80% of the users live farther than three miles from the springs and a recurring reason for drinking the spring water is that the taste is better than the water available at their homes. However, all the springs at some point tested positive for total coliform bacteria and all but one tested positive at least once for fecal coliform bacteria, meaning that 86% of the springs at some point did not meet U.S. municipal drinking water standards. None of the measured dissolved constituents exceeded drinking water standards, but one spring that exhibited elevated nitrate is downslope from a small cattle operation which may be affecting nutrient values in the water. Most of these springs appear to be fed by shallow, unconfined aquifers that are susceptible to contamination from nearby land uses that are not readily apparent from the roadside collection locations.